The Implementation of Islamic Religious Education Values in PAI Subjects to Develop a Superior Generation at SMPN 2 Raman Utara, Lampung - Lu’luyatul A’la; Hernisawati Hernisawati; M. Sayydul Abrori (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to analyze the implementation of Islamic educational values to shape a superior generation in the learning process at SMPN 2 Raman Utara. The approach used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results show that Islamic Religious Education (PAI) teachers play a central role in instilling Islamic values such as monotheism, morals, honesty, discipline, and responsibility through learning activities and religious habits in schools. The implementation of these values is reinforced by tadarus activities, congregational prayers, and teacher role models in behavior. Obstacles faced include the lack of religious facilities and the limited understanding of Islamic values among non-PAI teachers. This study recommends strengthening collaboration between teachers, principals, and parents in building a religious culture in schools.